The only efficient instrument : American women writers & the periodical, 1837-1916 - Cane, Aleta Feinsod, 1949-; Alves, Susan, 1958- (University of Iowa Press, 2001)
"The Only Efficient Instrument" examines farsighted women writers in nineteenth-century America whose pioneering use of newspapers and magazines had a vital impact on the political and intellectual communities of their day."